Investigation of Impulse Voltage on the Thermally Aged Empty Fruit Bunches (EFB) Fiber Paper Immersed in Transformer Oil - Fatin Nazirah, Hanapi; Ja’afar, Adnan; Nur Sabrina, Suhaimi; Mohd Taufiq, Ishak; Nurul ‘Izzati, Hashim; Rushdan, Ibrahim (2022)
Empty Fruit Bunch (EFB) from palm oil residue is one of the materials with development potential. The tensile strength and lightning impulse tests of Kraft paper are compared in this paper to those of unrefined and refined EFB fibre insulation papers aged at 90oC and 140oC, respectively. The performance of the insulation paper should be prioritised by impregnating it with transformer oil (mineral oil) and ageing it for 30 days at 90oC and 140oC. To undergo the impulse breakdown testing, a multistage impulse generator is used with the increment of 1 kV charging voltage for the first test and 2 kV charge voltage for the second test. Lianapac Measure (v15.5.1e) and CCK-2712 controller (100) software are used to observe the result of the impulse breakdown. In comparison to Kraft insulating paper, refined EFB paper has a higher tensile strength than unrefined EFB and Kraft paper. However, as the temperature of ageing increased, the trend of EFB decreased gradually. When it comes to lightning impulse tests, refined EFB paper performs better than Kraft paper. This demonstrates the potential for refined EFB paper to replace Kraft paper in transformer insulation systems.